Experimental Signal analysis of robot impacts in a fractional calculus perspective - Lima, Miguel F. M. (2019)
This paper presents a tudy of the signals captured during impacts and vibrations of a mechanical manipulator. In order to acquire and study the signnals an experimental setup is implemented. The system acquires data from the sensors, in real time, and processes it throught an off-line analysis package. The study is developed based on a set of signal processing tools, such as the Fast Fourier Transform and the windowed Fourier transform. The signals whose Fourier apectrum presents a non integer behavior are pointed out and analyzed using several time windows. The experimental results provide useful information that can assist in the design of a control system to deal with the unwanted effects of vibrations.